Physiotherapy Management in a Post-Caesarean Section Patient with Lower Limb Oedema and Mobility Limitation: A Case Report - Tsabitah Syahla Khairunisa; Tiara Fatmarizka; Sudarmi Sudarmi (Asosiasi Dosen Muda Indonesia, 2026)
The rate of delivery through Sectio Caesarea (SC) continues to increase globally and is often followed by postoperative problems such as incision pain, lower extremity oedema, impaired mobility, and difficulties in early lactation. These conditions may delay postpartum recovery and reduce maternal functional independence. Comprehensive physiotherapy intervention is therefore important to support early recovery after SC. Objective: This case report aimed to describe the outcomes of a comprehensive physiotherapy management program in a post-SC patient with lower extremity oedema and functional mobility limitation. Methodology: This study used a case report design involving a 28-year-old primigravida woman who underwent SC due to post-term pregnancy and cephalopelvic disproportion. Clinical data were collected through physiotherapy assessment, direct observation, and follow-up evaluation during 72 hours of hospitalization. The intervention program was arranged using the FITT principle and included deep breathing exercise, static contraction, ankle pumping exercise, leg elevation, early mobilization, breast massage, and oxytocin massage. Outcomes were evaluated using the Numeric Rating Scale, figure-of-eight method, clinical mobility observation, lactation status, and Barthel Index. Findings: After intervention, movement pain decreased from NRS 6/10 to 1/10, while the Barthel Index improved from 15, indicating total dependence, to 65, indicating moderate dependence. The patient was able to perform transfers and walk 5–10 meters with supervision. Lactation also improved gradually. However, changes in lower extremity oedema were minimal during the observation period. Implication: This case suggests that early and structured physiotherapy management may support pain reduction, mobility improvement, functional independence, and lactation support after SC. Originality: This report provides an integrated description of physiotherapy management for multiple early postpartum problems during short-term inpatient rehabilitation.